Efficiency and Effectiveness of Earmarking for Public Health in the Philippines - Miharu Jay Kimwell; Frances Lois Ngo; Vicente Alberto Puyat; George Douglas Siton (Philippine Institute for Development Studies (PIDS), 2022)
The Sin Tax Reform Act (STRA) of 2012 (RA 10351) and its amendments paved the way to revisit excise taxation for sin products, such as tobacco, alcohol, heated tobacco products and vapor products, and sweetened beverages. The ad valorem tax system reform has a two-fold aim: (1) increase revenues for public spending on health; and (2) reduce the burden of tobacco smoking and alcohol use. This study has attempted to examine the quality of spending of earmarked funds by the Philippine public health sector, and in doing so, to identify constraints to efficient and effective use. In particular, this study utilized a modified intersectoral framework focusing on four key criteria for evaluating the implementation of the earmarking policy: adequacy, efficacy, equity, and effectiveness. Although the STRA has brought about improvements in program and health outcomes, there is a need to revisit policies and processes to reap the benefits of earmarked funds adequately, efficiently, equitably, and effectively in the public health sector.
Keywords: 330; earmarking; Sin Tax; health financing; universal health coverage